1998
DOI: 10.1007/s004060050031
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicides of inpatients with depressive psychoses

Abstract: Research on identifying the relevant risk factors for suicides is faced with a multitude of methodological problems. The present study attempts to improve on some of these problems and to isolate those risk factors that are accessible in the early stages of the treatment of inpatients. A total of 3792 inpatients with monopolar or bipolar depression were treated during the period 1981-1992. Suicides (n=33) and controls (n=3759) were compared with respect to 77 sociodemographic and anamnestic variables and 195 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
0
21
0
3
Order By: Relevance
“…Twenty–six papers describing 24 studies contained data about suicidal ideation in people who subsequently died by suicide and suitable controls in groups of patients identified as having either one of the mood disorders or a schizophrenia spectrum psychosis. The 24 studies included in the analysis were made up of 13 studies of patients with schizophrenia spectrum psychosis , 10 studies of patients with mood disorders , and one study that reported on both diagnostic groups separately . Hence, there were 14 studies of patients with schizophrenia spectrum psychosis and 11 studies of mood disorders available for meta‐analysis (see Tables and ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty–six papers describing 24 studies contained data about suicidal ideation in people who subsequently died by suicide and suitable controls in groups of patients identified as having either one of the mood disorders or a schizophrenia spectrum psychosis. The 24 studies included in the analysis were made up of 13 studies of patients with schizophrenia spectrum psychosis , 10 studies of patients with mood disorders , and one study that reported on both diagnostic groups separately . Hence, there were 14 studies of patients with schizophrenia spectrum psychosis and 11 studies of mood disorders available for meta‐analysis (see Tables and ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study, with a small number of suicides, recorded the presence of suicidal ideation and suicide among both patients with schizophrenia spectrum psychosis and those with mood disorders in the same region and using the same methods . Two further pairs of studies examined similar patient groups and used similar methods . The way suicidal ideation was defined and recorded might have differed between diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies have found that suicide occurs in between 0.14%–0.32% of all psychiatric inpatients, while suicides are found to occur with a frequency of 0.08%–0.19% per admission [16,34,35,36,37]. …”
Section: Prevalence Rates and Time Change Of Inpatient Suicidementioning
confidence: 99%
“…Most studies have reported rates of inpatient suicide per number of admissions or patients, probably because this type of data is easier to collect through routine clinical data. Inpatient rates have been estimated to be between 54 and 404 suicides per 100,000 admissions [31,34,36,37,38,39,40,41,42,43] and between 127 and 332 suicides per 100,000 patients [35,37,43,44,45]. Expectedly, rates calculated per inpatient are higher than rates calculated per admission, as one patient can have more than one admission.…”
Section: Prevalence Rates and Time Change Of Inpatient Suicidementioning
confidence: 99%
See 1 more Smart Citation